Experimental and theoretical identification of the Fe(vii) oxidation state in FeO4−. Issue 45 (4th November 2016) - Lu, Jun-Bo; Jian, Jiwen; Huang, Wei; Lin, Hailu; Li, Jun; Zhou, Mingfei
Abstract : Two isomers of iron tetraoxygen anion, dioxoiron peroxide [(η 2 -O2 )FeO2 ] − and tetroxide FeO4 − were characterized by experiment and theoretical calculations, with heptavalent Fe(vii ) oxidation state identified in the later. Abstract : The experimentally known highest oxidation state of iron has been determined to be Fe(vi ) so far. Here we report a combined matrix-isolation infrared spectroscopic and theoretical study of two interconvertible iron oxide anions: a dioxoiron peroxide complex [(η 2 -O2 )FeO2 ] − with a C 2v -structure and a tetroxide FeO4 − with a D 2d tetrahedral structure, which are formed by co-condensation of laser-ablated iron atoms and electrons with O2 /Ar mixtures at 4 K. Quantum chemistry theoretical studies indicate that the Jahn–Teller distorted tetroxide FeO4 − anion is a d 1 species with hereto the highest iron formal oxidation state Fe(vii ).